Retrospective evaluation of toceranib phosphate (Palladia) in cats with oral squamous cell carcinoma. Issue 2 (February 2017) - Wiles, Valerie; Hohenhaus, Ann; Lamb, Kenneth; Zaidi, Bushra; Camps-Palau, Maria; Leibman, Nicole
Objectives: The aim of the study was to determine the clinical benefit and adverse event profile of toceranib phosphate in the treatment of feline oral squamous cell carcinoma (FOSCC). Methods: Data obtained from the medical records of cats with oral squamous cell carcinoma diagnosed between 2010 and 2014 treated with toceranib phosphate were compared with medical record data from cats that did not receive toceranib, cytotoxic chemotherapy or radiation, to determine the response to toceranib treatment and adverse event profile of toceranib in cats. Concurrent use of non-steroidal anti-inflammatory drugs (NSAIDs) was allowed. Results: Forty-six cats with FOSCC were included; 23 received treatment with toceranib (group 1) and 23 did not (group 2). The overall biological response rate in group 1 was 56.5%. Median survival time of toceranib-treated cats was significantly longer at 123 days compared with 45 days in cats not treated with toceranib ( P = 0.01). Cats achieving stable disease or better on toceranib therapy had significantly longer progression-free survival ( P <0.0001) and median survival ( P = 0.0042) times than those with progressive disease on toceranib. Administration of NSAIDs was also associated with significantly improved survival time ( P = 0.0038) among all cats. Anorexia was common but may reflect the underlying disease in these patients. Toceranib was well tolerated in cats, with the most common side effect being mild gastrointestinal toxicity. Conclusions and relevance: Toceranib was well tolerated in cats with oral squamous cell carcinoma and may lead to improved survival times, especially when combined with NSAIDs. NSAID administration was also associated with improved survival times, and the relative benefit of toceranib and NSAIDs is difficult to determine from this retrospective study. Despite improvement in survival times, long-term survival in this patient population remained poor. As toceranib was well tolerated and may improve survival time, prospective evaluation of toceranib alone is warranted to assess response as a single agent and as part of multimodal therapy in an effort to achieve a more durable response in FOSCC.